(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The development of closed-system farming presents promising solution enhance agricultural productivity, animal welfare, and food security in rural areas. This study aims to analyze the challenges, potentials, and strategies for developing closed-system farming in the Sangeh Region, Badung Regency, Bali. The research method involved conducting in-depth interviews with farm owners, managers, and farmers in one of the closed-system farms in the region. The interview results indicate that closed-system farming faces challenges such as resource availability, limited infrastructure, and inadequate understanding of technology. However, closed-system farming also holds significant potential for improving resource efficiency, product quality, and agricultural sustainability. Based on these findings, it is recommended that local government, agricultural industries, research institutions, and local communities collaborate to provide the necessary financial, technical, and educational support to develop closed-system farming in the region. Thus, the implementation of closed-system farming in Badung Regency enhance farmer welfare, food security, and environmental protection.